2021
DOI: 10.1111/jcmm.16679
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin attenuates intracerebral hemorrhage‐induced early brain injury possibly by PI3K/Akt signal activation‐mediated suppression of NF‐κB pathway

Abstract: Intracerebral hemorrhage (ICH) can induce intensively oxidative stress, neuroinflammation, and brain cell apoptosis. However, currently, there is no highly effective treatment available. Puerarin (PUE) possesses excellent neuroprotective effects by suppressing the NF‐κB pathway and activating the PI3K/Akt signal, but its role and related mechanisms in ICH‐induced early brain injury (EBI) remain unclear. In this study, we intended to observe the effects of PUE and molecular mechanisms on ICH‐induced EBI. ICH wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 79 publications
(322 reference statements)
0
14
0
Order By: Relevance
“…In the discrimination trial, the novel object (%) and familiar object (%) in the sham + progesterone group increased compared with the sham + vehicle group [ 59 ]. In addition, LY294002, as a commonly used inhibitor of the PI3K/Akt pathway, has been used in ICH with relatively mature application, and it is generally believed that it will not cause side effects or benefits in non-ICH area [ 60 , 61 ]. Overall, the current study showed that progesterone and LY294002 had no significant effect on the neurological function in normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…In the discrimination trial, the novel object (%) and familiar object (%) in the sham + progesterone group increased compared with the sham + vehicle group [ 59 ]. In addition, LY294002, as a commonly used inhibitor of the PI3K/Akt pathway, has been used in ICH with relatively mature application, and it is generally believed that it will not cause side effects or benefits in non-ICH area [ 60 , 61 ]. Overall, the current study showed that progesterone and LY294002 had no significant effect on the neurological function in normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…The neurological scores were assessed using the modified Garcia test and beam balance test [25]. The Modified Garcia score (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) was the sum of 6 separate trial scores, including spontaneous activity (scores 0-3), symmetry (0-3), forelimb extension (0-3), climbing (1-3), body proprioception (1-3), and response to vibrators (1-3). Beam balance test was used to record the distance rats walked on a balance beam in a quiet environment, scoring 0-4.…”
Section: Neurological Scorementioning
confidence: 99%
“…Puerarin is a type of flavonoid glycoside extracted from the Pueraria lobata root [ 8 ]. Studies have shown that puerarin has neuroprotective effects in several central nervous system diseases, including Parkinson’s disease [ 9 ], Alzheimer’s disease [ 10 ], acute spinal cord injury [ 11 ], brain ischemia/reperfusion injury [ 12 , 13 ], and intracerebral hemorrhage [ 14 ]. As an antioxidant to protect the cells against apoptosis caused by oxidative stress [ 15 ], Puerarin was shown to preserve the activities of antioxidant enzymes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 showed that puerarin was well bound to ER protein with the binding energy of −7.3 kcal/mol and induced the expression of reporter luciferase through an ER-mediated mechanism. Nevertheless, botanic drug puerarin may exhibit antiinflammatory and cytoprotective activities through regulating different signaling pathways, including phosphoinositide 3kinase (PI3K)/Akt pathway, NF-κB pathway and peroxisome proliferator-activated receptor (PPAR) pathway (He et al, 2019;Zeng et al, 2021). Our group previously found that puerarin might exhibit neuroprotective and neurorestorative activities via progesterone receptor (PR) signaling (Zhao et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%